Altered hemispheric lateralization of white matter pathways in developmental dyslexia: Evidence from spherical deconvolution tractography. (March 2016) - Zhao, Jingjing; Thiebaut de Schotten, Michel; Altarelli, Irene; Dubois, Jessica; Ramus, Franck
Abstract: This study examines the structural integrity and the hemispheric lateralization patterns of four major association fiber pathways in a group of French dyslexic children and age-matched controls (from 9 to 14 years), using high angular diffusion imaging combined with spherical deconvolution tractography. Compared with age-matched controls, dyslexic children show increased hindrance-modulated oriented anisotropy (HMOA) in the right superior longitudinal fasciculus (SLF). They also show a reduced leftward asymmetry of the inferior fronto-occipital fasciculus (IFOF) and an increased rightward asymmetry of the second branch of the SLF (SLF II). The lateralization pattern of IFOF and SLF II also accounts for individual differences in dyslexic children's reading abilities. These data provide evidence for an abnormal lateralization of occipito-frontal and parieto-frontal pathways in developmental dyslexia.